Rheumatoid arthritis: hand function, activities of daily living, grip strength and essential assistive devices. - I Shipham (AOSIS, 2003)
Persons with rheumatoid arthritis use assistive devices to enable them, in spite of impaired hand dexterity and grip strength, to manage Activities of Daily Living (ADL).